Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
Step-by-step explanation:
To prove that the sum of the first n even +ve integers is:
[tex]\mathsf{2+4+6+8+ . . . +2n = n^2+ n }[/tex]
By using mathematical induction;
For n = 1, we get:
2n = 2 × 1 = 2
2 = 1² + 1 ----- (1)
∴ the outcome is true if n = 1
However, let assume that the result is also true for n = k
Now, [tex]\mathsf{2+4+6+8+. . .+2k = k^2 + k --- (2)}[/tex]
[tex]\mathsf{2+4+6+8+. . .+2k+2(k+1)}[/tex]
we can now say:
[tex]\mathsf{= (k^2 + k) + 2(k + 1)} \\ \\ \mathsf{= k^2 + k + 2k + 1}[/tex]
[tex]\mathsf{= (k^2 + 2k + 1) + (k + 1)}[/tex]
[tex]\mathsf{= (k + 1)^2 + (k + 1)}[/tex]
∴
[tex]\mathsf{2 + 4 + 6 + 8 + . . . + 2k + 2(k + 1) = (k + 1)^2 + (k + 1)}[/tex]
Thus, the result is true for n = m+1, hence we can posit that the result is also true for each value of n.
As such [tex]\mathsf{2+4+6+8+. . .+2n = n^2 + n }[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.